ANALISIS PERAN AKTOR DALAM PENGEMBANGAN PROGRAM REVITALISASI SMK NEGERI 6 SEMARANG - Bunga Adhitiyana Sari; Tri Yuniningsih (Journal of Public Policy and Management Review, 2021)
Revitalization of Vocational High Schools Program is one of the government’s strategies in increasing competitiveness of Indonesian human resources in facing global challenges as a result of Industrial Revolution 4.0, based on Presidential Instruction Number 9 of 2016 concerning Revitalization of Vocational High Schools in the context of Improving the Quality and Competitiveness of Indonesian Human Resources. Vocational High School 6 Semarang as one of nationally referral Vocational High Schools in Revitalization of Vocational High Schools Program, involving many actors in the implementation process. The purpose of this study was to identify actors, the role of actors, the stages of the actor-network, and the model of actor-network that formed in the Development Program of Revitalization of Vocational High School 6 Semarang. The research method used in this study is qualitative descriptive. The results showed that there were 13 actors involved before Vocational High School 6 Semarang became self-managed; started from bureaucracy, judicial institutions, pressure groups, and community organizations; which were further classified as primary actors and secondary actors. Actors carried out their role as informant, consultant, partner, or control. The stages of the actor-network that was formed started from Punctualization, Translation, Problematization, Interessment, Enrollment, Inscription, Speaker/Delegate, Betrayal and Irreversibility. The model of actor-network formed in the form of Penta Helix. The results also showed that the change in the status of the development Program of Revitalization of Vocational High School 6 Semarang to be self-managed, requiring the adjustment toward actors who were involved and their roles as well as having an impact on the actor-network and the model of actor-network that have been formed. The implementation of the program, until now, is yet to be optimal and requires an improvement efforts from actors that are still involved in the development program.